2014
DOI: 10.1530/joe-14-0067
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning actions of aldosterone through p38 signaling modulation in isolated rat hearts

Abstract: Although persistent excessive actions of aldosterone have unfavorable effects on the cardiovascular system, primarily via mineralocorticoid receptor (MR)-dependent pathways, the pathophysiological significance of aldosterone cascade activation in heart diseases has not yet been fully clarified. We herein examined the effects of short-term aldosterone stimulation at a physiological dose on cardiac function during ischemia-reperfusion injury (IRI). In order to study the effects of aldosterone preconditioning, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…In our study, we found that aldosterone inhibited PPARα and adiponectin protein expression and promoted inflammation and insulin resistance in cardiomyocytes; however, in contrast to muscle cells, p38MAPK protein expression was increased in the cardiomyocytes. MR blockade with eplerenone reversed these effects, and this finding accords with those of recent studies that demonstrated that aldosterone stimulates the p38MAPK signaling pathway in rat podocytes [32] and that the inhibition of PPARα increases IL-18 expression in cardiomyocytes [33]. Therefore, it is possible that p38MAPK and PPARα are both involved in MR-induced adiponectin expression in cardiomyocytes.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, we found that aldosterone inhibited PPARα and adiponectin protein expression and promoted inflammation and insulin resistance in cardiomyocytes; however, in contrast to muscle cells, p38MAPK protein expression was increased in the cardiomyocytes. MR blockade with eplerenone reversed these effects, and this finding accords with those of recent studies that demonstrated that aldosterone stimulates the p38MAPK signaling pathway in rat podocytes [32] and that the inhibition of PPARα increases IL-18 expression in cardiomyocytes [33]. Therefore, it is possible that p38MAPK and PPARα are both involved in MR-induced adiponectin expression in cardiomyocytes.…”
Section: Discussionsupporting
confidence: 88%
“…in order to eliminate suffering. The heart was then rapidly excised, and the aorta was cannulated onto a Langendorff apparatus, followed by retrograde-perfusion at a constant pressure (80 mmHg) with modified Krebs-Henseleit buffer, as previously described [ 3 , 13 – 15 ]. A water-filled balloon catheter was introduced into the left ventricle to record various hemodynamic parameters.…”
Section: Methodsmentioning
confidence: 99%
“…in order to eliminate suffering. The heart was then rapidly excised, and the aorta was cannulated onto a Langendorff apparatus, followed by retrograde-perfusion at a constant pressure (80 mmHg) with modified Krebs-Henseleit buffer (11 mM glucose, 118 mM NaCl, 4.7 mM KCl, 2.0 mM CaCl 2 , 1.2 mM MgSO 4 , 1.2 mM KH 2 PO 4 , 25 mM NaHCO 3 , 0.5 mM EDTA), as previously described [7,11,26]. A temperature-regulated heart chamber was then placed around the heart in order to keep the perfused heart at a certain temperature.…”
Section: Experiments In Langendorff Heartsmentioning
confidence: 99%
“…Creatine phosphokinase (CPK) levels were measured in the effluent using an enzymatic activity assay, as previously described [7,26]. Values were corrected for coronary flow and heart weight [CPK (U/l) × coronary flow (l/min)/heart weight (g) = U/min/g].…”
Section: Cardiac Enzyme Measurementmentioning
confidence: 99%
See 1 more Smart Citation